Neural Correlates of Anosognosia in Alzheimer's Disease and Mild Cognitive Impairment: A Multi-Method Assessment - Tondelli, Manuela; Barbarulo, Anna M.; Vinceti, Giulia; Vincenzi, Chiara; Chiari, Annalisa; Nichelli, Paolo F.; Zamboni, Giovanna (Frontiers in Behavioral Neuroscience, 2018)
Patients with Alzheimer’s Disease (AD) and Mild Cognitive Impairment (MCI) may present anosognosia their cognitive deficits. Three different methods have been historically used to measure anosognosia in patients with AD and MCI, but no previous studies have established if they share similar neuroanatomical correlates. The purpose of this study was to investigate if anosognosia scores obtained with the three most commonly used methods to measure anosognosia relate to focal atrophy in AD and MCI patients, in order to improve understanding of the neural basis of anosognosia in dementia. Anosognosia was evaluated in 27 patients (15 MCI and 12 AD) through clinical rating (Clinical Insight Rating Scale, CIRS), patient-informant discrepancy (Anosognosia Questionnaire Dementia, AQ-D), and performance discrepancy on different cognitive domains (self-appraisal discrepancies, SADs). Voxel-based morphometry correlational analyses were performed on magnetic resonance imaging (MRI) data with each anosognosia score. Increasing anosognosia on any anosognosia measurement (CIRS, AQ-D, SADs) was associated with increasing grey matter atrophy in the medial temporal lobe including the right hippocampus. Our results support a unitary mechanism of anosognosia in AD and MCI, in which medial temporal lobes play a key role, irrespectively of the assessment method used. This is in accordance with models suggesting that anosognosia in AD is primarily caused by a decline in mnemonic processes.